SEED YIELD AND QUALITY OF FENUGREEK (TRIGONELLA FOENUM-GRAECUM L.) CV. LAM METHI-2 AS INFLUENCED BY INTEGRATED NUTRIENT MANAGEMENT - M. ANITHA,; D. V. SWAMI,; D. R. SALOMI SUNEETHA, (The Bioscan, 2014)
A field experiment was conducted to evaluate the yield and quality aspects of fenugreek seed under different combinations of manures and fertilizers application in college farm, HC & RI, during rabi season. Seed yield in the presence of 50% inorganic fertilizers and 50% organic manures along with bio-ferrtilizer inoculation to seed reached maximum value (721.40 kg ha-1). There is no significant difference in the treatment combinations for germination percentage and speed or rate of germination. Other quality parameters like seedling length, vigour index, seedling dry weight and protein content (9.36 mg/100g) reaching maximum in the combination of 50% inorganic fertilizers and 50% organic manures (viz., poultry manure, vermi compost, neem cake, FYM) and bio- fertilizers inoculation.